Using Nicotine Gum to Assist Nondaily Smokers in Quitting: A Randomized Clinical Trial. Issue 3 (24th April 2019) - Shiffman, Saul; Scholl, Sarah M; Mao, Jason; Ferguson, Stuart G; Hedeker, Donald; Primack, Brian; Tindle, Hilary A
Abstract: Introduction: Non-daily intermittent smokers (ITS) comprise 30% of US adult smokers. ITS smoke for nicotine and have trouble quitting, but tend to smoke in particular situations. This study tested the effect of nicotine gum, used to prevent or react to situational temptations, for helping ITS quit. Methods: ITS (smoking 4–27 days/month) seeking help quitting were randomized to 2 mg nicotine gum ( n = 181) or placebo ( n = 188), to be used to anticipate or react to temptations to smoke, for 8 weeks. Participants received up to six sessions of behavioral counseling. The primary outcome was 6-month biochemically verified continuous abstinence; analyses also examined 14-day point-prevalence abstinence at multiple time points, and used event-history analyses to assess progression to abstinence, lapsing, and relapsing. Analyses adjusted for group differences in age and baseline smoking, and considered several potential moderators of treatment effects. Results: Nicotine gum did not significantly improve outcomes on any measure. Biochemically verified 6-month continuous abstinence rates were 7.2% for active gum and 5.3% for placebo (AOR = 1.39, 0.58–3.29, p > .25). ITS with any degree of dependence (Fagerstrom Test of Nicotine Dependence scores >0) showed poorer outcomes on multiple endpoints, and did more poorly on active gum on some outcomes. Gum use was low, starting at 1 gum per day on average and declining over time. Conclusions: Nicotine gum (2 mg), used intermittently, did not improve cessation rates among ITS, including those demonstrating some degree of dependence. Implications: Nicotine replacement has been extensively tested with daily smokers, especially those who smoke relatively heavily. Nondaily smoking is now common, creating a need for treatment for ITS. Despite evidence that ITS' smoking is motivated by nicotine-seeking, a theoretically and empirically derived situational approach to using acute nicotine replacement was not successful at helping ITS quit. Gum use was low; whether higher or more frequent dosing is needed, or whether an entirely different approach is needed, is not clear. Effective treatment options are needed for ITS, especially those with some degree of dependence.